PD-L1 is associated with the prognosis of penile cancer: A systematic review and meta-analysis - Lu, Yi; Wang, Yutao; Su, Hao; Li, Hongjun (Frontiers in Oncology, 2022)
Background: Previous studies have explored the role of PD-L1 in the survival outcomes of penile cancer patients with controversies existed. Thus, the meta-analysis was conducted to report and review the association between PD-L1 and survival in penile cancer patients. Methods: PubMed, Cochrane Library, EMBASE, and Web of Science were all searched, screened, and reviewed by June 1, 2022. Hazard ratio (HR) was used to evaluate the relationship between PD-L1 and survival outcome, and odds ratio (OR) was for tumor features. Results: Nine retrospective studies (1,003 patients) were incorporated. The prevalence of PD-L1 in patients with penile cancer was 51.4% (95% CI = 42.1%-60.8%, I2 = 88.5%). Higher PD-L1 on tumor cells was related to shorter cancer-specific survival (CSS) in patients (HR = 1.578, 95% CI = 1.227-2.029, I2 = 23.3%), but had no associations with overall survival (OS) (HR = 1.123, 95% CI = 0.511-2.465, I2 = 0.0%). Subgroup analysis indicated that higher PD-L1 was related to shorter CSS in Caucasus (HR = 1.827, 95% CI = 1.355-2.465, I2 = 0.0%) only. Furthermore, PD-L1 had associations with tumor stage (pT1 vs. pT2-4, OR = 0.480, 95% CI = 0.346-0.667, P = 0.001) and tumor grade (Poor vs. Well and moderate, OR = 2.655, 95% CI = 1.859-3.790, P < 0.001). PD-L1 positivity was also related to lymph node (LN) status (pN0/NX vs. pN1–3, OR = 0.541, 95% CI = 0.385-0.759, P = 0.001) and HPV status (Positive vs. Negative, OR = 0.510, 95% CI = 0.322-0.810, P = 0.003). A trend toward statistical significance between PD-L1 and histological types was also observed (Usual SCC vs. Others, OR = 1.754, 95% CI = 0.984-3.124, P = 0.070). Conclusions: PD-L1 over-expression was related to worse survival outcomes and several clinicopathological features of penile cancer. PD-L1 expression can be applied to select appropriate treatment strategies for penile malignancies.